Blinatumomab vs historic standard‐of‐care treatment for minimal residual disease in adults with B‐cell precursor acute lymphoblastic leukaemia. (24th January 2020) - Gökbuget, Nicola; Dombret, Hervé; Giebel, Sebastian; Brüggemann, Monika; Doubek, Michael; Foa, Robin; Hoelzer, Dieter; Kim, Christopher; Martinelli, Giovanni; Parovichnikova, Elena; Maria Ribera, Josep; Schoonen, Marieke; et al.
Abstract: Objectives: Survival outcomes from a single‐arm phase 2 blinatumomab study in patients with minimal residual disease (MRD)‐positive B‐cell precursor (BCP)‐acute lymphoblastic leukaemia (ALL) were compared with those receiving standard of care (SOC) in a historic data set. Methods: The primary analysis comprised adult Philadelphia chromosome (Ph)‐negative patients in first complete haematologic remission (MRD ≥ 10 −3 ). Relapse‐free survival (RFS) and overall survival (OS) were compared between blinatumomab‐ and SOC‐treatment groups. Baseline differences between groups were adjusted by propensity scores. Results: The primary analysis included 73 and 182 patients from the blinatumomab and historic data sets, respectively. When weighted by age to the blinatumomab‐treatment group, median RFS was 7.8 months and median OS was 25.9 months in the SOC‐treated group. In the blinatumomab study, median RFS was 35.2 months; median OS was not evaluable. Propensity score weighting achieved balance with seven baseline prognostic factors. With adjustment for haematopoietic stem cell transplantation (HSCT) status, a 50% reduction in risk of relapse or death was observed with blinatumomab vs SOC. Median RFS, unadjusted for HSCT status, was 35.2 months with blinatumomab and 8.3 months with SOC. Conclusions: These analyses suggest that blinatumomab improves RFS, and possibly OS, in adults with MRD‐positive Ph‐negative BCP‐ALL vs SOC.